Russian Contributions to International Humanitarian Law A contrastive analysis of Russia's historical role and its current practice - Riepl, Michael (Kölner Schriften zum Friedenssicherungsrecht - Cologne Studies on International Peace and Security Law - Études colonaises sur le droit de la paix et de la sécurité internationale, 2022)
Has Russia turned from "Paul to Saul" with regards to international humanitarian law (IHL)? This book aims to answer this question by contrasting the past and the present. Firstly, it offers a comprehensive account of the remarkable Russian contributions to IHL since 1850. Secondly, it analyses Russia's current approach to IHL, drawing on a wide range of legislation, case law, diplomatic records, and military practice. Finally, the author contrasts the past and the present - not without embedding his findings in the changed context of our time. The book is aimed at international law experts as well as people interested in legal history. Its author is an IHL researcher and practitioner with extensive experience in the post-soviet world.